The construction of a myth. Suárez in the Portuguese and Spanish press (1984-2014) - Langa-Nuño, Concha (Historia y Política, 2022)
The former Prime Minister of Spain, Adolfo Suárez, has become one of the founding myths of Spanish democracy in recent years. In spite of leaving the government in 1981, in great disrepute, when the former president died he was presented in all the media as the true architect of the Transition to democracy, and as a model of political virtues. In this paper we aim to study the construction of the narrative about Suárez and his memory after his departure from government. To do so, we have chosen five dates that we believe can clearly show such path: his resignation; his actions in the 23F; his definitive resignation from politics with the CDS; the awarding of the Prince of Asturias Prize; and his death. For the analysis we have chosen the newspapers with the highest circulation in Spain and Portugal between 1981 and 2014. We have intended to carry out a comparative study to see whether the memory of Suárez also changed abroad. After our analysis, we have been able to verify that the steps in the construction of the myth began a few weeks after his departure, almost through the back door of politics, in the 23F coup d’état. His departure from politics allowed his figure to be appreciated without partisanship, and then the recognition and awards came. His death, in the midst of the political crisis, increased the value of his figure, which was also influenced by the nostalgia for the Transition as a period of harmony and consensus and the need for symbols of unity among Spaniards.
Keywords: Adolfo Suárez; democratic transition; newspapers; memory